2021
DOI: 10.1038/s41598-021-92998-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strength and hydrostatic testing of VIVO adhesive in sutureless microsurgical anastomoses: an ex vivo study

Abstract: Conventional anastomoses with interrupted sutures are challenging and inevitably associated with trauma to the vessel walls. The goal of this study was to evaluate a novel alternative adhesive-based suture-free anastomosis technique that uses an intraluminal stent. Overall, 120 porcine coronary vessels were analyzed in an ex vivo model and were examined for their mechanical (n = 20 per cohort) and hydrostatic strength (n = 20 per cohort). Anastomoses were made using the novel VIVO adhesive with an additional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It is mentioned that this mechanism of action is due to the strong electronegative charge on the cyanoacrylate monomer that reacts with the positively charged carbohydrate capsule of Gram-positive organisms [ 36 , 37 ]. The polyurethane-based tissue adhesive was previously evaluated in an ex vivo study showing good tensile strength in suture-less microsurgical anastomoses [ 38 ]. Other in vivo studies also showed that it can be a good candidate as a reinforcement for blood vessel anastomoses in a secure and less traumatic manner [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is mentioned that this mechanism of action is due to the strong electronegative charge on the cyanoacrylate monomer that reacts with the positively charged carbohydrate capsule of Gram-positive organisms [ 36 , 37 ]. The polyurethane-based tissue adhesive was previously evaluated in an ex vivo study showing good tensile strength in suture-less microsurgical anastomoses [ 38 ]. Other in vivo studies also showed that it can be a good candidate as a reinforcement for blood vessel anastomoses in a secure and less traumatic manner [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…VIVO showed a fast polymerization and was able to induce a significantly faster sealing with a bleeding time of about 3 min compared with fibrin glue, with a bleeding time of about 10 min (Tanaka et al, 2017). Furthermore, in vitro porcine coronary studies on sutureless microsurgical anastomoses with VIVO showed that the adhesive could withstand pressures up to 299 mmHg, which was found to be comparable to native vessels (Heitzer, Brockhaus, et al, 2021). In a rat study, microsurgical anastomoses with VIVO and two additional sutures in the carotid artery demonstrated 100% overall patency rate over a 2‐h period, with no evidence of stenosis or invasion of adhesive into the vessels lumen (Heitzer, Mohlhenrich, et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Other promising synthetic adhesives that are being investigated in preliminary studies are adhesives based on polyurethanes (Fukushima et al, 2018; Heitzer, Brockhaus, et al, 2021; Heitzer, Mohlhenrich, et al, 2021; Tanaka et al, 2017). These polymers consist of two main components: Isocyanates and polyols.…”
Section: Introductionmentioning
confidence: 99%
“…It was designed to polymerizes quickly with the aid of a curing agent to overcome the above‐mentioned downsides. This adhesive already demonstrated sufficient burst and tensile strength in sutureless microsurgical anastomoses in an ex vivo setting 19 . Furthermore, it was used in combination with a temporary intraluminal catheter or a nitinol stent in an in vivo rat model to develop faster, easier, more secure and less traumatic methods for microvascular anastomoses 20 …”
Section: Introductionmentioning
confidence: 99%
“…This adhesive already demonstrated sufficient burst and tensile strength in sutureless microsurgical anastomoses in an ex vivo setting. 19 Furthermore, it was used in combination with a temporary intraluminal catheter or a nitinol stent in an in vivo rat model to develop faster, easier, more secure and less traumatic methods for microvascular anastomoses. 20 In the present study, the adhesive is further investigated using a porcine animal model to achieve a higher comparability to the human.…”
mentioning
confidence: 99%